Respuesta :

Answer:

y = -1/3x + 6[tex]\frac{2}{3}[/tex]

Step-by-step explanation:

First, change the original equation to slope intercept form:

y + 4 = 3x

y = 3x - 4

Now, find the slope of the perpendicular line. It will be the opposite reciprocal:

The opposite reciprocal of 3 is -1/3.

Next, plug this into the slope intercept equation along with the given point, so we can solve for b:

y = mx + b

6 = -1/3(2) + b

6 = -2/3 + b

6.67 = b

So, the equation will be y = -1/3x + 6[tex]\frac{2}{3}[/tex]